Implementing goals of care conversations with veterans in VA long-term care setting: a mixed methods protocol. (December 2015) - Sales, Anne; Ersek, Mary; Intrator, Orna; Levy, Cari; Carpenter, Joan; Hogikyan, Robert; Kales, Helen; Landis-Lewis, Zach; Olsan, Tobie; Miller, Susan; Montagnini, Marcos; Periyakoil, Vyjeyanthi; et al.
Abstract Background The program "Implementing Goals of Care Conversations with Veterans in VA LTC Settings" is proposed in partnership with the US Veterans Health Administration (VA) National Center for Ethics in Health Care and the Geriatrics and Extended Care Program Offices, together with the VA Office of Nursing Services. The three projects in this program are designed to support a new system-wide mandate requiring providers to conduct and systematically record conversations with veterans about their preferences for care, particularly life-sustaining treatments. These treatments include cardiac resuscitation, mechanical ventilation, and other forms of life support. However, veteran preferences for care go beyond whether or not they receive life-sustaining treatments to include issues such as whether or not they want to be hospitalized if they are acutely ill, and what kinds of comfort care they would like to receive. Methods Three projects, all focused on improving the provision of veteran-centered care, are proposed. The projects will be conducted in Community Living Centers (VA-owned nursing homes) and VA Home-Based Primary Care programs in five regional networks in the Veterans Health Administration. In all the projects, we will use data from context and barrier and facilitator assessments to design feedback reports for staff to help them understand how well they are meeting the requirement to have conversations with veterans about their preferences and to document them appropriately. We will also use learning collaboratives—meetings in which staff teams come together and problem-solve issues they encounter in how to get veterans' preferences expressed and documented, and acted on—to support action planning to improve performance. Discussion We will use data over time to track implementation success, measured as the proportions of veterans in Community Living Centers (CLCs) and Home-Based Primary Care (HBPC) who have a documented goals of care conversation soon after admission. We will work with our operational partners to spread approaches that work throughout the Veterans Health Administration.